2011
DOI: 10.4049/jimmunol.1003441
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: JAM-C Controls Homeostatic Chemokine Secretion in Lymph Node Fibroblastic Reticular Cells Expressing Thrombomodulin

Abstract: The development and maintenance of secondary lymphoid organs, such as lymph nodes, occur in a highly coordinated manner involving lymphoid chemokine production by stromal cells. Although developmental pathways inducing lymphoid chemokine production during organogenesis are known, signals maintaining cytokine production in adults are still elusive. In this study, we show that thrombomodulin and platelet-derived growth factor receptor α identify a population of fibroblastic reticular cells in which chemokine sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 22 publications
(18 reference statements)
1
13
0
Order By: Relevance
“…This finding implies that the currently used FRC phenotype description (Pdpn + CD31 − ) may obscure the true diversity of stromal cells in SLOs. This interpretation has been confirmed in a recent study that defines a particular FRC subpopulation through JAM-C controlled chemokine secretion (Frontera et al, 2011). Using genetic tools such as BAC transgenic mouse lines with stromal cell-specific promoters will help to define both function and phenotype of SLO stromal cells in future studies.…”
Section: Discussionsupporting
confidence: 61%
“…This finding implies that the currently used FRC phenotype description (Pdpn + CD31 − ) may obscure the true diversity of stromal cells in SLOs. This interpretation has been confirmed in a recent study that defines a particular FRC subpopulation through JAM-C controlled chemokine secretion (Frontera et al, 2011). Using genetic tools such as BAC transgenic mouse lines with stromal cell-specific promoters will help to define both function and phenotype of SLO stromal cells in future studies.…”
Section: Discussionsupporting
confidence: 61%
“…As chemokines are in part synthesized by lymphoid stromal cells including FRCs, CCL21 detected in tissue sections could be preferentially localized inside FRC conduits for transport to the HEV network, where it may contribute to lymphocyte recruitment. [30][31][32][33][34] Thus, 2-P microscopy imaging helps to uncouple in vitro chemoattractant responsiveness from in vivo chemoattractant responsiveness, which depends on the "usable" chemokine levels available to trafficking lymphocytes. At the same time, these data highlight the importance of chemokine receptor levels in responding to presumably limited amounts of stromal chemokine.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Frontera et al. found that a subset of thrombomodulin‐expressing FRCs coexpressed JAM‐C in murine lymph nodes. The authors reported that this subpopulation of FRCs expressed the highest levels of mRNA for CCL19, CCL21a, and CXCL12.…”
Section: Contact‐dependent Regulation Of Stromal Cell Functionmentioning
confidence: 99%